ナンキョク チイキ カンソク ニ カンスル ツウシン ブモン ホウコク 1 - 河原, 猛夫; カワハラ, タケオ; 中西, 光二; ナカニシ, コウジ; 秋山, 拡; アキヤマ, ヒロシ; 有竹, 秀一; アリタケ, シュウイチ; 二条, 弼基; ニジョウ, タネモト; 加藤, 安太郎; カトウ, ヤスタロウ; et al. (国立極地研究所, 1958)
P(論文) departmental bulletin paper